Aspects of Economic Relations between India and North Africa. Issue 2 (July 2012) - Azhar, Muhammad
In the globalised world, the importance of co-operation between different regions and countries of the world has grown very fast. Although India and the countries of North Africa are situated at a long distance but the economic relations have prospered significantly. India is the second fastest growing economy in the world with substantial mass of skilled manpower, whereas the countries of North Africa are rich in phosphate deposits and petroleum oil and gas deposits. They are situated on the eastern side of the Mediterranean across which lies the Europe. They are also part of the African continent. Thus geography gives them a strategic position. India's economic relations with these countries are quite old. However, the period of analysis is of contemporary years. The article tries to find the trends in India – North Africa trade, India's exports to North African countries, India's imports from North Africa, balance of trade and cooperation in energy and other sectors. The competition in North African market is very high but Indian companies can utilize the North African market for expanding access to the markets of other African countries and European Countries.